Operational Result After Modified Weaver Dunn (W.D) Procedure In Chronic Acromio-Clavicular (A.C) Joint Disruption - Muhammad Khalid Ur Rehman, Aadil Amin, Muhammad Usman Aslam, Nauman Abbas, Mian Muhammad Hanif (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In orthopedic trauma acromioclavicular joint disruptions are among the most commonly faced injuries that could be due to sports or road traffic accidents. These are injuries in which treatment is always controversial especially in type III of Rockwood type. These injuries accounts for 12% of the total shoulder injuries with young male patients have predominance. Aim: To assess the operational result after acromioclavicular joint fixation with Modified Weaver Dunn procedure using tight roping technique with two endobuttons. Place and duration of study: Department of Orthopedic Surgery, Govt. Shahdrah Teaching Hospital Lahore and Lahore General Hospital Lahore for one year from 01st July 2019 to 30th June 2020. Methodology: This is a descriptive case series study of 10 patients in the combined settings of Department of Orthopedic Surgery Govt. Shahdrah Teaching Hospital Lahore and Lahore General Hospital Lahore. All the cases were operated by a single surgeon using Modified WD procedure with endo-buttons and tight roping technique and operational result was assessed by using Oxford shoulder scoring system (OSS), this system was used in pre-operative and post-operative settings and results were compared. SPSS version 23 & paired t test was used for the analysis of results of all the patients in both pre and post-operative settings. Results: The patient’s average age was 34±2. Road traffic accidents and sports injuries to the shoulders were mechanism of injuries. In 70% of cases dominant side was involved. The significant p value is found in the pre and post-operative oxford shoulder score. Conclusion: There is a consequential improvement in OSS in all the patients. However small number of follow ups and lesser patients were the reasons of our limited study that need to be looked upon in near future.